2022
DOI: 10.1186/s41687-022-00410-9
|View full text |Cite
|
Sign up to set email alerts
|

Do patient-reported outcome measures measure up? A qualitative study to examine perceptions and experiences with heart failure proms among diverse, low-income patients

Abstract: Background The Kansas City Cardiomyopathy Questionnaire (KCCQ) is a Patient-Reported Outcome Measure (PROM) used to evaluate the health status of patients with heart failure (HF) but has predominantly been tested in settings serving predominately white, male, and economically well-resourced populations. We sought to examine the acceptability of the shorter version of the KCCQ (KCCQ-12) among racially and ethnically diverse patients receiving care in an urban, safety-net setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The KCCQ questionnaire does not assess mental and social aspects of heart failure-related patient-reported outcomes. 28 Therefore, incorporating the SDoH risk assessment into routine clinical practice would not overlap with the KCCQ-12 questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The KCCQ questionnaire does not assess mental and social aspects of heart failure-related patient-reported outcomes. 28 Therefore, incorporating the SDoH risk assessment into routine clinical practice would not overlap with the KCCQ-12 questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of patients with heart failure, although receptive to using the PROM provided, participants expressed that the PROM did not adequately capture key issues such as mental health and social relationships. (Davis et al 2022) A study of patients with lung cancer showed that the PROM did not capture the complexity of the symptom of breathlessness including experiential dimensions (Ji Hyun Sung et al 2020). Thus, clinicians are at risk of not exploring distress more globally, including psycho-existential distress, and vice versa.…”
Section: Symptom-centered Assessment In a Person-centered Processmentioning
confidence: 99%
“…In this context, patient-reported outcomes, such as health-related quality of life (QoL), and functional outcomes, such as exercise capacity, are also greatly impaired and strongly correlate with clinical outcomes. Importantly, these two functional status measures are considered highly relevant outcomes from the patient’s and healthcare professional’s perspective [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%